Molecular etiology study of hearing loss in 13 Chinese Han families - Sun, Lianhua; Lin, Zhengyu; Wang, Xiaowen; Shen, Jiali; Li, Yue; Huang, Yuyu; Yang, Jun (Frontiers in Neurology, 2022)
Hearing loss affecting about 2/1000 newborns is the most common congenital disease. Genetic defects caused approximately 70% of patients who have non-syndromic hearing loss. We recruited 13 Chinese Han deafness families who tested negative for GJB2, SLC26A4, and mitochondrial 12S rRNA. The probands of each family were performed whole-exome sequencing (WES) or targeted next-generation sequencing (NGS) for known deafness genes to study for pathogenic causes. We found four novel mutations of CDH23, one novel mutation of MYO15A, one novel mutation of TMC1, one novel mutation of PAX3, and one novel mutation of ADGRV1, one novel CNV of ADGRV1, and one novel CNV of STRC. Hearing loss is a highly hereditary and heterogeneous disease. The results in the limited samples of this study show that Usher and Waardenburg syndrome-related genes account for a major proportion are strongly associated with Chinese Han hearing loss patients negative for GJB2, SLC26A4, and mitochondrial 12S rRNA, followed by STRC resulting in mild to moderate deafness.